2020
DOI: 10.33225/jbse/20.19.1092
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Pre-Service Teachers’ Reception and Attitudes Towards Virtual Laboratory Experiments in Life Sciences

Abstract: This research reports the assessment of pre-service teachers’ reception and attitudes towards virtual laboratory experiments in Life Sciences with the aim of advancing adaptability to digital learning. Using sequential mixed-methods in a quasi-experimental design, 68 pre-service teachers in the 3rd year of a Bachelor of Education (B.Ed) program were surveyed before and after virtual learning interventions. This phase was followed by qualitative data gathering using focus group interviews with all participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…One of the misconceptions held by certain educators in IBL classrooms is the assumption that learners will autonomously direct their learning (Gholam, 2019). According to Penn (2020), some educators engage in enquiry-based practices due to their adherence to the guidelines provided in the Curriculum and Assessment Policy Statement (CAPS) about the implementation of classroom strategies. Moreover, arguably, educators have challenges in stimulating students' curiosity and engagement with a subject matter before granting them the opportunity to pursue an autonomous investigation or collaboration with peers (Eltanahy, 2019).…”
Section: Challenges Of Using Enquiry-based Learning In Teaching Life ...mentioning
confidence: 99%
“…One of the misconceptions held by certain educators in IBL classrooms is the assumption that learners will autonomously direct their learning (Gholam, 2019). According to Penn (2020), some educators engage in enquiry-based practices due to their adherence to the guidelines provided in the Curriculum and Assessment Policy Statement (CAPS) about the implementation of classroom strategies. Moreover, arguably, educators have challenges in stimulating students' curiosity and engagement with a subject matter before granting them the opportunity to pursue an autonomous investigation or collaboration with peers (Eltanahy, 2019).…”
Section: Challenges Of Using Enquiry-based Learning In Teaching Life ...mentioning
confidence: 99%
“…experiments include: (1) investigating the relationship of force and surface area to the magnitude of pressure; (2) investigating the relationship of mass to the magnitude of pressure, (3) investigating the effect of activity (depth, acceleration of gravity, and density) on hydrostatic pressure, (4) investigating Archimedes' law, (5) investigates the conditions for objects to float, float, and sink, (6) investigate Pascal's law, (7) investigate the concept of gas pressure (air) and the relationship between altitude and air pressure, ( 8) analyze the principle of pressure in everyday life. Opinion expressed by: Prihatiningtyas, (2013); Mubarok & Mulyaningsih, (2014); Sinulingga et al, (2016); Saputra et al,(2020); Hung & Tsai, (2020), stated that applying the PhET simulation program in science learning activities and learning research Herga et al, (2015); Suleman & Kumar, (2019); Penn & Mavuru, 2020;Said et al, (2020), found that there was a correlation between conducting virtual experiments that would have an impact on students' science skills.…”
Section: Discusionmentioning
confidence: 99%
“…Keterampilan tersebut merupakan indkator yang sangat penting dalam melihat kemampuan peserta didik dengan cara menghubungkan hasil pengamatan, mencari perbedaan, ciri khas, mencari kesamaan, Keterampilan mengelompokkan adalah bagian dari kegiatan seperti menemukan perbedaan, ciri-ciri, menemukan persamaan, membandingkan, dan menemukan klasifikasi dasar.Tujuan dari mengidentifikasi kelompok adalah untuk memudahkan dalam memahami beberapa peristiwa, segala sesuatu dalam hidup, dan untuk mengidentifikasi berbagai jenis kelompok dengan lebih mudah. Beberapa hasil penelitian telah dilaporkan bahwa dengan melatihkan keterampilan klasifikasi maka akan meningkatkan sikap ilmiah, literasi sains, literasi numerik, berpikir tingkat tinggi (Oykum, 2020;Penn., Mavuru, 2020;Sezen, 2017;Shao-Na et al, 2019) Tabel 12, menjelaskan skor setiap indikator KPS murid SDN di Tompo Bulu, ditemukan bahwa skor rata-ratanya mulai yang tertinggi sampai terendah berturut-turut, prediksi, merancang percobaan, interpretasi data, berhipotesis, mengontrol variable,menyimpulkan, mengukur, klasifikasi, observasi, dan mengkomunikasikan hasil percobaan.…”
Section: Percentage Of Agrrementunclassified